Fiscal developments and financial stress: a threshold VAR analysis - Afonso, António (2022)
We use a threshold VAR analysis to study the linkages between changes in the debt ratio, economic activity and financial stress within different financial regimes. We use quarterly data for the US, the UK, Germany and Italy, for the period 1980:4– 2014:1, encompassing macro, fiscal and financial variables, and use nonlinear impulse responses allowing for endogenous regime-switches in response to structural shocks.The results show that output reacts mostly positively to an increase in the debt ratio in both financial stress regimes; however, the differences in estimated multipliers across regimes are relatively small. Furthermore, a financial stress shock has a negative effect on output and worsens the fiscal situation. The large time-variation and the estimated nonlinear impulse responses suggest that the size of the fiscal multipliers was higher than average in the 2008–2009 crisis.